Les homicides entre délinquants : une analyse des conflits qui provoquent des règlements de comptes - Cordeau, Gilbert (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
Certain conflicts between offenders over their illicit activities end in the murder of one of the protagonists. These homicides are refered to as settling of accounts. This article examines why and under what circumstances offenders choose to solve their differences by a settling of accounts. Three categories of conflicts between offenders were identified. The 444 cases of settling of accounts ending with 531 victims that occured in Quebec from 1970 to 1986 were analyzed within those categories. The findings indicate that these homicides occured in cases where the stakes were very high. This study also shows why certain criminal activities and certain illicit markets give rise to more settling of accounts than others.